(untitled) (Economic and Political Thought, 2014)
Mainstream economics is based on the following assumptions: 1. Homo economicus is motivated by self-interest in economic activities; 2. The main actors in the market are enterprises and households; 3. The main goal of an enterprise is always and only to maximize profit. Contemporary literature indicates, however, that over time, these assumptions have been challenged. In addition, the neoclassical economics theory alleged that there seems to be a lack of ethical and cultural aspects. The aim of this paper is to identify what determines setting objectives that go beyond profit maximization. Organizational culture, which largely depends on the owners and top managers, is a key determinant. M. Noga confirms that organizational culture is an element that determines the growth and development of enterprises. This subject is important both from the scientific and practical point of view. We are witnessing in the economy that there is a shortage of knowledge about the cultural context in managing and how to measure social welfare, which is insufficiently taking into account the qualitative elements of socio-economic development. The study defines organizational culture as well as noneconomic activities. Then dimensions of culture are characterized, especially taking into account the characteristics that contribute to undertaking noneconomic activities. The paper contains the results of empirical research, which verify the theoretical assumptions and confirm the diversity of the objectives set by contemporary enterprises.